To Test, Perchance to Diagnose: Practical Strategies for Severe Acute Respiratory Syndrome Coronavirus 2 Testing. (2nd March 2021) - Humphries, Romney M; Azar, Marwan M; Caliendo, Angela M; Chou, Andrew; Colgrove, Robert C; Fabre, Valeria; Ginocchio, Christine C; Hanson, Kimberly E; Hayden, Mary K; Pillai, Dylan R; Pollock, Nira R; Lee, Francesca M
Abstract: Testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in symptomatic and asymptomatic patients is an important component of the multifaceted approach of managing the coronavirus disease 2019 pandemic. Determining how to best define testing strategies for different populations and incorporating these into broader infection prevention programs can be complex. Many circumstances are not addressed by federal, local, or professional guidelines. This commentary describes various scenarios in which testing of symptomatic or asymptomatic individuals for SARS-CoV-2 virus (antigen or ribonucleic acid) can be of potential benefit. Consideration to pretest probability, risks of testing (impact of false-positive or false-negative results), testing strategy, as well as action based on test results are explored. Testing, regardless of setting, must be incorporated into overarching infection control plans, which include use of personal protective equipment (eg, masks), physically distancing, and isolation when exposure is suspected. Abstract : Optimal testing strategies for SARS-CoV-2 have been a topic of considerable discussion. No one approach addresses testing in all scenarios. This review describes practical approaches for testing based on pre-test probability, anticipated actions from test results, and infection control and prevention activities in a variety of testing scenarios.